Aspek Keamanan dan Privasi Penerapan Informed Consent Elektronik di Unit Kamar Bedah RSU Anna Medika Madura Bangkalan - M. Afif Rijal Husni (Poltekkes Kemenkes Semarang, 2022)
Medical records are useful as legal evidence, essential to ensure their safety and privacy. Electronic medical records do not yet have specific laws and regulations, generally regulated in Permenkes No. 269 of 2008 on Medical Records. Informed consent is often used as legal evidence and is always made in paper form (Hatta, 2017). Informed consent made electronically needs to be studied related to its implementation and use, more specifically on the aspects of security and privacy. This research is qualitative research of phenomenology. The data collection method used in-depth interviews with 9 staffs as key and main informants. The security aspect of electronic informed consent , the data is stored in a database on the server computer. Each officer in each service is given a username and password to access the menu in the electronic system according to the service unit. The security aspects of electronic devices are divided into software and hardware. Software security is done by periodic data backups, installation of antivirus software, and the use of firewalls and encryption. Hardware security is done quite well but there are still many that are not up to standard. In the aspect of electronic informed consent privacy there is an SPO that regulates its use. Each user is given a username and password to access the electronic system in accordance with his authority. Every officer at RSU Anna Medika Madura is sworn to maintain the confidentiality of health information that is legally consistent if violated, including IT vendors who assist in the implementation of electronic systems accompanied by stamped signatures